2021
DOI: 10.3390/inventions7010005
|View full text |Cite
|
Sign up to set email alerts
|

Production of PP Composites Reinforced with Flax and Hemp Woven Mesh Fabrics via Compression Molding

Abstract: Hemp and flax fibers are among the most interesting vegetable fibers that can be used to reinforce polymeric matrices. In line with the global environmental requests, the use of these fibers especially coupled with thermoforming polymers are increasing more and more in order to expand their applications and replace synthetic fibers and thermosetting plastics. However, one of the major limitations of vegetable fibers is their poor adhesion with polymeric matrices that is often overcome by fibers chemical treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…43 Otherwise compression molding is the natural choice for thermoforming composites and other heterogeneous polymer-based systems. [44][45][46]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Otherwise compression molding is the natural choice for thermoforming composites and other heterogeneous polymer-based systems. [44][45][46]…”
Section: Discussionmentioning
confidence: 99%
“…Normally vacuum forming is performed on “single‐component” polymers, although the technique has also been applied on sandwich structures 43 . Otherwise compression molding is the natural choice for thermoforming composites and other heterogeneous polymer‐based systems 44–46 …”
Section: Discussionmentioning
confidence: 99%
“…Due to their higher mechanical performance, flax fibers are mostly combined with glass fibers [55] or carbon fibers [56]. However, they can also be combined with other natural fibers, including hemp fibers [57,58], to preserve their recyclabil-ity and to be able to classify them as biocomposites [38]. However, hemp fibers are not as strong as flax fibers, and because of this, the most used synthetic fiber for hybrid hemp fiber composites is glass fibers [26,59].…”
Section: Macrostructure Of Natural Fibersmentioning
confidence: 99%
“…In these studies, mostly mechanical properties such as impact, shear stress, and tensile stress was analyzed and investigate with the different binders. 15,16 The studies of various binders has been reported such as biodegradable polymers, 17 polyethylene, 18 epoxies, 19,20 polypropylene, [21][22][23] polybutylene adipate-co-terephthalate, 24 polyamide PA 11, 25 and so forth. In most of the studies, different compatibilizers and plasticizers were used to improve the mechanical properties of binders.…”
Section: Introductionmentioning
confidence: 99%